Geospatial variation in caesarean delivery - Jennifer Vanderlaan; Johnathan A. Edwards; Anne Dunlop (Wiley, 2020)
Abstract Aim The purpose of this study was to evaluate the variation in caesarean delivery rates across counties in Georgia and to determine whether county‐level characteristics were associated with clusters. Design This was a retrospective, observational study. Methods Rates of primary and repeat caesarean by maternal county of residence were calculated for 2008 through 2012. Global Moran's I (Spatial Autocorrelation) was used to identify geographic clustering. Characteristics of high and low‐rate counties were compared using student's t test and chi‐squared test. Results Spatial analysis of both primary and repeat caesarean rate identified the presence of clusters (Moran's I = 0.375; p < .001). Counties in high‐rate clusters had significantly lower access to midwives, more deliveries paid by Medicaid, higher proportion of births for women belonging to racial/ethnic minority groups and were more likely to be rural.